O063 Impact of sleep deprivation on distributed team performance and cohesion. (9th November 2022) - Greer, E; Matthews, R; Owen, M; Grosser, L; Roma, P; Banks, S
Abstract: Distributed teams often have limited contact resulting in less effective collaboration and decreased cohesion. Those in 24/7 industries are further impacted by fatigue and sleep loss which threatens workers' safety, productivity, and performance. To date little is known about distributed team cohesion with extended periods of time awake. Hence, this study examined the impact of sleep deprivation on distributed team performance and cohesion. 22 healthy individuals (M=22.81, SD=4.4 years, 11f) aged 18-45 years participated in a five-day sleep study. Participants were randomly allocated into teams consisting of four members and underwent 62h of total sleep deprivation (TSD). Distributed teams completed the COHESION task at 10h intervals throughout the wake period. COHESION required distributed teams to attempt resource movements, while avoiding visible and invisible barriers. Team members could dedicate time to reveal barriers to all, making successful resource movements easier. Distributed team performance was assessed using team successful resource movements. Distributed team cohesion was assessed through team members' barrier reveal responses in relation to their total responses. Data were analysed using linear mixed models. Results showed that distributed team cohesion decreased with TSD (F(5, 495.19)=3.18, p=.008), and there were significant differences between teams (F(5, 21.99)=8.74, p<.001). Team performance also decreased with TSD (F(5, 144)=3.01, p=.013), with significant differences between teams (F(5, 21.01)=7.03, p<.001). This study found distributed team cohesion was reduced with TSD, as was overall team performance. We found each distributed team used a different strategy to manage the team task during sleep deprivation and these differences impacted their overall team performance.